SYNTHESIS AND CHARACTERIZATION OF HYDROXYPROPYL CELLULOSE-CYSTEAMINE CONJUGATE AS A NOVEL CATIONIC THIOMER WITH LIPOPHILIC PROPERTIES - Rahmat, Deni; Rahman, Fikry A. R.; Nurhidayati, Liliek; Laksmitawati, Dian Ratih (International Journal of Applied Pharmaceutics, 2019)
Objective: Thiomers have been known as polymer with mucoadhesive properties. The aim of this study was to synthesize the mucoadhesive potential of hydroxypropyl cellulose-cysteamine conjugate (HPC-cysteamine). Methods: The parent polymer HPC was chemically modified by introducing sulphydryl bearing compound using reductive amination. HPC-cysteamine conjugates were prepared at reaction pH value of 5. The reaction was stabilized by the addition of cyanoborohydride. Afterwards, the conjugate was evaluated for optimum free thiol group, swelling behavior, viscosity and mucoadhesive properties. Results: The conjugates showed maximum thiol incorporation on HPC of 1063.03±64.27 µmol/g. The disulphide groups content was 278.71±32.14 μmol/g. Mucoadhesion studies revealed that mucoadhesion of HPC-cysteamine demonstrated 26 h. The swelling behaviour of HPC-cysteamine tablets increased within the time period of study. The viscosity of HPC-cysteamine was higher than that of unmodified HPC. The thermal profile of HPC-cysteamine and unmodified HPC analyzed by differential scanning calorimetry (DSC) displayed a different enthalpy (ΔH) value. Conclusion: HPC-cysteamine conjugate renders better properties which might be more beneficial for drug delivery system compared to unmodified HPC.